2019
DOI: 10.14449/jbd.2019.7.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Febrile Neutropenia in Advanced Breast Cancer Patients Receiving Adjuvant Docetaxel-Doxorubicin-Cyclophosphamide Chemotherapy in Korea and Its Impact on Prognosis

Abstract: Purpose: The concurrent regimen of docetaxel, doxorubicin, and cyclophosphamide (TAC) has been categorized as a high-risk factor for febrile neutropenia (FN). The incidence of FN was reported to be as high as 17%-26% in studies conducted in Western countries. However, these rates may vary among different ethnic groups. This study aimed to evaluate the incidence of FN and its effect on prognosis following adjuvant TAC chemotherapy in Korean patients with advanced breast cancer. Methods: We analyzed data from 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
1
1
1
Order By: Relevance
“…Previous studies conducted in Western countries reported that the overall incidence of FN during adjuvant TAC chemotherapy was 17%–26% [ 8 10 11 23 ], and clinical guidelines have categorized this regimen as conferring a high risk (> 20%) of FN [ 13 14 15 ]. However, the overall frequency of FN in Korean breast cancer patients receiving adjuvant TAC chemotherapy was a significantly higher than that in patients in previous studies conducted in Western countries (42.5%–63.4% vs. 17%–26%) [ 18 19 20 ]. Ethnic differences in hematologic toxicity from the TAC regimen are associated with inter-individual and inter-ethnic variations of docetaxel and doxorubicin pharmacokinetics or pharmacodynamics due to genetic differences [ 24 25 ].…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Previous studies conducted in Western countries reported that the overall incidence of FN during adjuvant TAC chemotherapy was 17%–26% [ 8 10 11 23 ], and clinical guidelines have categorized this regimen as conferring a high risk (> 20%) of FN [ 13 14 15 ]. However, the overall frequency of FN in Korean breast cancer patients receiving adjuvant TAC chemotherapy was a significantly higher than that in patients in previous studies conducted in Western countries (42.5%–63.4% vs. 17%–26%) [ 18 19 20 ]. Ethnic differences in hematologic toxicity from the TAC regimen are associated with inter-individual and inter-ethnic variations of docetaxel and doxorubicin pharmacokinetics or pharmacodynamics due to genetic differences [ 24 25 ].…”
Section: Discussioncontrasting
confidence: 56%
“…Previous studies conducted in Korea reported that the overall frequency of FN during adjuvant TAC chemotherapy was significantly higher than that observed in previous studies conducted in Western countries (42.5%–63.4% vs. 17%–26%) [ 18 19 20 ]. However, only 1 study with a small sample size reported the clinical effect of primary prophylactic therapy using pegfilgrastim on the incidence of FN during adjuvant TAC chemotherapy in Korea [ 21 ].…”
Section: Introductionmentioning
confidence: 68%
“…Hasil penelitian Zhou et al, (2017) menunjukkan bahwa terjadi efek samping berupa neutropenia akibat penggunaan regimen kemoterapi paclitaxel+platinum sebanyak 51 pasien (38,9%) dari total 131 pasien. Park et al, (2019) juga membuktikan bahwa regimen kemoterapi adjuvan taxan+antrasiklin pada ca mammae dapat menginduksi terjadinya efek samping berupa neutropenia. Total 102 pasien dalam penelitian tersebut mengalami efek samping berupa neutropenia sebanyak 64 pasien (62,8%).…”
Section: Karakteristik Pasienunclassified